Untangling the Conformational Polymorphism of Disordered Proteins Associated With Neurodegeneration at the Single-Molecule Level - Birol, Melissa; Melo, Ana M. (Frontiers in Molecular Neuroscience, 2020)
A large fraction of the human genome encodes intrinsically disordered proteins/regions (IDPs/IDRs) that are involved in diverse cellular functions/regulation and dysfunctions. Moreover, several neurodegenerative disorders are associated with the pathological self-assembly of neuronal IDPs, including tau (Alzheimer’s disease), alpha-synuclein (Parkinson’s disease) and huntingtin exon 1 (Huntington’s disease). Therefore, there is an urgent and emerging clinical interest in understanding the physical and structural features of their functional and disease states. However, their biophysical characterization is inherently challenging by traditional ensemble techniques. Firstly, unlike globular proteins, IDPs lack stable secondary/tertiary structures under physiological conditions and may interact with multiple and distinct biological partners, subsequently folding differentially, thus contributing to the conformational polymorphism. Secondly, amyloidogenic IDPs display a high aggregation propensity, undergoing complex heterogeneous self-assembly mechanisms. In this review, we discuss the advantages of employing cutting-edge single-molecule fluorescence techniques to characterize the conformational ensemble of three selected neuronal IDPs (huntingtin exon 1, tau and alpha-synuclein). Specifically, we survey the versatility of these powerful approaches to describe their monomeric conformational ensemble under functional and aggregation-prone conditions, and binding to biological partners. Together, the information gained from these studies provides unique insights into the role of gain- or loss-of-function of these disordered proteins in neurodegeneration, which may assist the development of new therapeutic molecules to prevent and treat these devastating human disorders.